Perancangan Front End Dashboard Admin Website Investa Mengenai Platform Investasi Pertanian Menggunakan Metode Iterative incremental - Dini Dwi Andayani; Faishal Mufied Al-Anshary; Hanif Fakhrurroja (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
The current digitalization era is where technological conditions have developed in aspects of life. Information needs and activities can be collected easily in one platform that can help people communicate plans effectively. One of them is the agricultural capital loan system. Initially, people borrowed capital by going to cooperatives or banks where they borrowed money. In addition, farmers used to borrow farming equipment from nearby farm shops. Notarizable documents must be attached to the capital loan. Based on these problems, the author has a solution, Investa, a web-based platform that connects farmers and investors. The implemented features are suitable for the virtual representation of information and functions. Investa is planned according to the needs realized according to benchmarking and interview results. This design also has a dashboard to monitor the website. Investa's internal parties can only access the admin dashboard, so the admin receives more data from investors and farmers when accessing Investa. The design of the admin dashboard is made by considering the results of analysis. All the research that has been done produces output in software designs, such as UML diagrams and blueprint prototype designs. The result creates a dashboard website that uses the Iterative, incremental methodology, and the testing process is carried out using black box testing, UAT, and stress testing, which gets a total score of 90 with an average percentage of 86.25 which shows this platform is quite good in preparation for future dashboard development.